Testing a “Push-Pull” theory of work commitment among organizational professionals. - McAulay, Brian J.; Zeitz, Gerald (Social Science Journal, 2006)
Writers have suggested that the current trend toward decreased job security requires employees to commit more strongly to newly “professionalized” occupations to compensate for social and resource support no longer received from their employers. And it has sometimes been implied that such a shift toward increased professional commitment will arise naturally as organizational commitment is whittled away by perceived job insecurity. We propose that job insecurity does not automatically push the employee toward professional commitment, but rather that such commitment stems from the pull of perceived occupational professionalization. We construct a nonrecursive model proposing relationships between job insecurity, perceived professionalization, and both organizational and professional commitment. This model is supported (using structural equation modeling) in a study of 622 employees in 3 occupations: corporate law, human resource management, and computer programming, all of which can be considered professions or semiprofessions. Finally, we suggest how occupations can be fashioned better to support employees when faced with job insecurity and job loss. © 2006 Elsevier Inc. All rights reserved. Reprinted by permission of the publisher.